Determinants of Novice Investors in Deciding to Use Fundamental or Technical Analysis when Buying Shares - Sibarani, Blasius Erik (AKRUAL: JURNAL AKUNTANSI, 2023)
Introduction/Main Objectives: This study aims to see what factors decide novice investors in using fundamental and technical analysis when buying shares, that no one has researched novice investors and also what are the determinants of novice investors in deciding to use the analysis used by them, so this needs to be examined in order to prove what become a determinant of novice investors regarding the analysis used when buying shares. Background Problems: One of the things that makes young people interested in investing in financial markets (such as shares and bonds) is because of the return they receive as a return on the investment they make. In buying shares, novice investors should use analysis that is suitable for use, such as fundamental and technical. Novelty: This research provides an overview of starting to invest in shares so that they use an appropriate analysis for the shares of the company they want to buy, this research also provides an overview of evidence of how novice investors buy shares so that this can be used as a lesson for other people who want to invest in stocks, and this research give an overview related to fundamental and technical analysis in financial markets. Research Method: Data analysis use mean comparison to see each indicator's average score and significance in the decision to use fundamental or technical analysis when buying shares. Finding/Results: The research findings show that the main determinants of novice investors in deciding to use fundamental analysis when buying shares are liability, total equity, debt-to-equity ratio (DER), return on investment (ROI), and dividends, while the main determinants of novice investors in deciding to use technical analysis when buying shares namely price, moving average convergence divergence (MACD), and trading volume. Conclusion: The practical implications, namely research findings are useful for understanding novice investors who buy shares in the money market and also for people who want to get involved in the money market so as to help make the decisions they make.